2014
DOI: 10.1097/prs.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Training Institution on Academic Affiliation and Productivity among Plastic Surgery Faculty in the United States

Abstract: Identification of educational processes that encourage a career in academic practice may improve resident mentorship and resident interest in academic plastic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 27 publications
5
83
2
1
Order By: Relevance
“…6,7 For example, if an author has published 20 papers, and 12 of those papers have at least 12 citations (ie, the author's 13th paper has less than 13 citations), an author has an h-index of 12. Despite the fact that it was originally introduced in the physical sciences, recent studies in multiple specialties in academic medicine have validated the h-index, including radiology, 3,8 radiation oncology, 9 emergency medicine, 10 anesthesiology, [11][12][13] otolaryngology, 4,14,15 neurosurgery, 5,16 urology, 17 plastic surgery, 2,18,19 oral and maxillofacial surgery, 20 and hand surgery. 21 With literature continuing to support the use of the h-index in academic medicine, one must consider the influence of self-citation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 For example, if an author has published 20 papers, and 12 of those papers have at least 12 citations (ie, the author's 13th paper has less than 13 citations), an author has an h-index of 12. Despite the fact that it was originally introduced in the physical sciences, recent studies in multiple specialties in academic medicine have validated the h-index, including radiology, 3,8 radiation oncology, 9 emergency medicine, 10 anesthesiology, [11][12][13] otolaryngology, 4,14,15 neurosurgery, 5,16 urology, 17 plastic surgery, 2,18,19 oral and maxillofacial surgery, 20 and hand surgery. 21 With literature continuing to support the use of the h-index in academic medicine, one must consider the influence of self-citation.…”
mentioning
confidence: 99%
“…Recently, emphasis has shifted toward research quality, with new bibliometric measures available to quantify the impact of an author's work. [2][3][4][5] One of the most widely used and studied bibliometric measures focusing on quality of research is the Hirsch index or h-index. Hirsch introduced the h-index in 2005, and it is defined as the number of papers h with at least h or more citations.…”
mentioning
confidence: 99%
“…Studies have shown that residents who have been exposed to scientific research and paper writing during their residency are more likely to opt for careers in academic institutes as well as more likely to do research on their own. [4,18] This would obviously lead to the evolution of clinician-scientists and have a salutary effect on the development of translational research in India.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Since the quality of resident training directly affects the quality of clinical care and research, it becomes essential to monitor the skills acquired during the training period. [4][5][6] The most important of these domains would obviously be clinical care, procedural skills, and theoretical knowledge of the subject. The success of a training institute in imparting these skills, however, is difficult to evaluate; the required information is often not easily available.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gast et al showed that nearly 40% of the academic plastic surgeons in the United States graduate from only 11 (12%) residency programs. 9 This may be a result of clustering of highly productive academic faculty into only a few plastic surgery training programs. It is also possible that the applicants who are interested in academic practices focus their energies on securing training positions at one of the highly productive academic programs.…”
Section: Benefits Of Research During Residencymentioning
confidence: 99%